Semantik Prosodi Nomina Indonesia dalam Korpus Wacana Berita Arab Internasional Oman 2013 - Ilfia Rahmi Rasyid; Hanady Martha Laura; Fazlur Rachman (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2022)
The prosodic semantic analysis in this research focuses on the aura of the lexical and contextual meaning of words that collocate with the noun 'Indonesia', in the international news corpus of Omani Arabic "KALIMAT a Multipurpose Arabic Corpus, 2013". Using the AntConc corpus, two kinds of "Indonesian" nouns were found, "Indonesia" in the indefinite form /indu:ni: niyyah/ and in the definitive form /al-indu:ni: niyyah/. However, this study focuses on the noun "Indonesia" in the definitive form /al-indu:ni: niyyah/. The theory that is used in this study is the prosodic semantic theory proposed by Louw (1993), which states that the coloring or aura of the meaning of a form, is imbued with its collocations. The research design is descriptive qualitative and quantitative which is used to maximize the semantic analysis of the prosody of the research object. Based on the results of corpus data processing, it was found that 8 (eight) nouns collocated with 'Indonesian' nouns, namely /ba: li:/, /jazz: rah/, /asy-syurthah/, /al-Jindra:l/, /al -wathaniyyah/, /al-Musalaha/, /al-qua:t/, and /al- Hukumah/. From the results of the analysis, the authors found that the collocation of the noun 'Indonesia' is not only a single noun, it is also a phrase that gives a neutral and negative aura to the noun 'Indonesia'.Keywords - Prosody Semantics, Arabic Corpus, Collocation, Indonesia